1969
DOI: 10.1017/s0043174500054424
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption ofs-Triazines by Soil Organic Matter

Abstract: The adsorption of sevens-triazines from aqueous solutions by organic soil colloids was determined at pH levels from 1.0 to 5.2. Maximum adsorption occurred at pH levels in the vicinity of the pKAvalues of the respective compounds. The amounts adsorbed were dependent upon the molecular structures of the compounds and the pH of the suspension and were, in order of decreasing adsorption, as follows: 2-methoxy-4,6-bis(diethylamino)-s-triazine (hereafter referred to as tetraetatone) = 2,4-bis(isopropylamino)-6-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0
4

Year Published

1981
1981
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 37 publications
7
90
0
4
Order By: Relevance
“…Atrazine adsorption is seen to follow the titration curve closely, suggesting that undissociated carboxyl and phenol groups constitute the sites for atrazine adsorption. The importance of carboxyl and phenol groups as adsorption sites for various s-triazines has been pointed out previously (Weber et al, 1969;Hayes, 1970, Stevenson, 1972Adams, 1973;Senesi & Testini, 1982). although Muller-Wegener (1977) found a significant, but negative, correlation between ametryne adsorption and the phenol group content.…”
Section: Hirmic Acidmentioning
confidence: 89%
See 1 more Smart Citation
“…Atrazine adsorption is seen to follow the titration curve closely, suggesting that undissociated carboxyl and phenol groups constitute the sites for atrazine adsorption. The importance of carboxyl and phenol groups as adsorption sites for various s-triazines has been pointed out previously (Weber et al, 1969;Hayes, 1970, Stevenson, 1972Adams, 1973;Senesi & Testini, 1982). although Muller-Wegener (1977) found a significant, but negative, correlation between ametryne adsorption and the phenol group content.…”
Section: Hirmic Acidmentioning
confidence: 89%
“…to adsorb atrazine and other striazines has been demonstrated repeatedly (Walker & Crawford, 1%8;Weber et al, 1969;Hayes, 1970;Stevenson, 1972;hluller-Wegener, 1977;Streibig, 1979;Sencsi & Testini, 1982). The results of the present investigation, shown by dots in Fig.…”
Section: Hirmic Acidmentioning
confidence: 93%
“…Most studies on atrazine adsorption by soil or soil organic matter (Kovaios et al, 2006;Weber et al, 1969) suggest that hydrophobic partitioning and/or hydrogen bonds are involved.…”
Section: Interactions Of Triazine Herbicides With Hpvpecosemmt Composmentioning
confidence: 99%
“…Considering the negative correlation between adsorption and leachability, this finding appears to confirm the well-documented strong relationship between soil organic matter and adsorption of s-triazine herbicides. Numerous studies have shown that soil organic matter is the most important soil factor as far as atrazine adsorption or bioactivity is concerned (Talbert & Fletchall, 1965;Weber Weed & Ward, 1969;Harrison et at., 1976;Anderson, Stephenson & Corke, 1980;Nel & Reinhardt, 1984;Ehlers, Reinhardt & 1987. In several studies strong links between the mobility of terbuthylazine in soil and the soil organic matter content have Downloaded by [University of Connecticut] at 19:46 11 October 2014 S.…”
Section: Resultsmentioning
confidence: 99%